Virtual exchange: a promising high-impact practice for developing intercultural effectiveness across disciplines - Nannette Evans Commander; Wolfgang F. Schloer; Sara T. Cushing (University of Groningen Press, 2022)
Virtual Exchange (VE), a pedagogy that uses technology to facilitate online, collaborative work among students and their peers in other countries, is viewed as a high-impact practice contributing to engaged learning and student success in higher education. This study investigates the impact of various types of VE on the intercultural effectiveness skills of undergraduate and graduate students enrolled in courses across disciplines. The relationship between VE and intercultural skills for minority and non-minority students was also investigated, along with the relationship between dosage (length and duration) of VE and intercultural skills. Results indicate VE positively impacts the development of intercultural skills of students and that there were no differences when the data are disaggregated by individual classes or disciplinary areas. There were no significant differences for minority and non-minority students and for the impact of dosage, but further research is recommended for these two important topics. Findings of this study underline the generalizability of VE across disciplines and its suitability for providing wider access to international experiences for all students.